Photodynamic therapy of vaginal intraepithelial neoplasia—How to do it? - Xiaoyun Wang; Haixia Qiu; Huiqi Zhan; Zheng Huang (Photodiagnosis and Photodynamic Therapy)
Vaginal intraepithelial neoplasia (VaIN or VAIN), a rare precancerous disease, is difficult to treat. Photodynamic therapy (PDT) is a relatively new modality for the treatment of various precancerous mucosal lesions of the lower genital organs, including VaIN. Due to the special structure and location of the vagina, it is difficult to apply photosensitizer and light irradiation to VaIN lesions. This article provides a tutorial guide on the application of ALA-mediated intravaginal PDT for the treatment of VaIN lesions under different situations.